GOOGLE SITES AS AN E-LEARNING MODULE FOR ONLINE LEARNING: A MODE OF CHOICE DURING THE COVID-19 PANDEMIC - Indri Eka Pertiwi; Pupung Purnawarman (PROJECT (Professional Journal of English Education), 2023)
Covid-19 has forced teachers and students, globally and in Indonesia, to experience unprecedented ways of teaching and learning. Online platforms became a mode of choice for all. Google Sites is a cutting-edge platform that gives hopes and promises to help teachers develop materials. This study is intended to investigate how Google sites as an e-module works in the classroom and how students perceive it. A descriptive qualitative design is employed, involving sixteen senior secondary students. It gathers data from document analysis and interviews, which are further analyzed qualitatively. The study shows that Google Sites offers various features allowing students to have video of particular topic explanation, do quizzes, and submit their assignments. Positive response from the students towards it is also portrayed in the interview results. The students think that Google Sites is quite helpful, interesting, interactive, and easy to use. Unstable internet connection, however, is mentioned to be an aspect limiting their activity in using it. Keywords:  Google Sites; E-Module; Covid-19